A framework for evaluating depth perception in stereoscopic virtual environments - Silva, Sahra K G; Correa, Cleber G; Lauretto, Marcelo S; Nunes, Fatima L S (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
Understanding humans’ notion of depth and how they interact with stereoscopic virtual environments is still a challenge. This context encompasses investigation about how features of these environments affect the human perception of depth. This perception is important during the execution of tasks, such as manipulating objects, which requires interpreting and understanding space-related information. Literature does not present general and flexible methods to measure such perception. This paper presents a general, extensible and flexible framework to assess the depth perception in different stereoscopic virtual environments that encompasses object manipulation tasks and visualization techniques. A study was conducted, considering three stereoscopy techniques (based on true anaglyph, color anaglyph and shutter glasses), twenty users, two immersive virtual environments (a simulator for dental anesthesia and a racing game), parameters (distance between user and virtual objects, virtual objects’ sizes) and metrics (hit rate, error rate, time and presence questionnaire responses). Results indicate that the framework produces consistent verdicts about depth perception provided by studied stereoscopic techniques. The approach has potential to assist developers in the decision making related to the choice of a stereoscopy technique for a virtual environment, considering benefits and limitations.